The Effect of Oil Price Shock and Inflation on Stock Returns: A Comparative Study on ASEAN-3 - Kristyaningrum, Agatha Canonia; Hersugondo, Hersugondo (Universitas Dian Nuswantoro Semarang, 2021)
This study aims to examine the effect of the WTI type oil price shock and inflation on stock returns from the ASEAN-3 capital markets, namely Indonesia, Thailand, and Philippines. The data used are monthly data from 2015 to 2019. The data analysis technique used is multiple linear regression. The results showed that oil price shocks had a significant positive effect on stock returns on the JASICA Mining index and the SET Resources index, but had no significant effect on the PSE Mining and Oil index. Furthermore, inflation had a significant positive effect on stock returns of Indonesia seen from the JASICA Mining index. Whereas, inflation had no significant effect on the SET Resources index of Thailand and the PSE Mining and Oil stock index of Philippines. Keywords: Oil price shock, Inflation, Stock return